José Revueltas, El luto humano. Ed. crít. y est. de Antonio Cajero Vázquez. El Colegio de San Luis, San Luis Potosí, 2014; 221 pp. - García Sánchez, Nayeli (El Colegio de México, 2016)
Se reseña el libro: El luto humano.